Different antibody isotypes against tuberculosis: what we know and what we need to know - Li, Huoming; Li, Hao (Frontiers in Immunology, 2025)
Humoral Immunity plays an important role during Mycobacterium tuberculosis(Mtb) infection. In mouse models, polyvalent and monoclonal antibodies targeting Mtb provided some protection against tuberculosis (TB). The five human antibody isotypes (IgG, IgM, IgA, IgE, and IgD) mediate an array of functional activities against bacterial infections, including neutralization, antibody-dependent cellular cytotoxicity (ADCC), phagocytosis, and complement activation. Different antibody isotypes have functions through different protective mechanisms based on the biological structures and pathways involved. In this review, we summarize the research progress on the different isotypes of antibodies against TB, and discuss the antibody-based strategies against tuberculosis, the potentiality of antibodies in TB diagnosis, and suggest further research directions, including investigating the mechanisms of different isotypes of antibody-mediated protection against TB, identifying correlates of immunity, and novel vaccines development.